Are Vitamin D Levels Lower in the Breast Milk of Bariatric Surgery Patients? [18N]. (May 2018) - Persad, Malini D.; Perseleni, Tatyana; Baker, David; Pimentel, Veronica; Buckley, Ayisha; Garretto, Diana
Abstract : INTRODUCTION: To determine if bariatric surgery is associated with lower levels of vitamin D in breast milk. METHODS: A prospective cohort study of pregnant women was conducted at a university hospital between June 2014 to July 2015. Included in the study were pregnant women with singleton gestations who had a history of bariatric surgery (gastric bypass group) and pregnant women with no history of malabsorption (controls). Samples collected included maternal postpartum blood, colostrum, transitional milk, and mature milk. Each sample was analyzed for 25-hydroxyvitamin D (25(OH)D) level. Parametric and nonparametric statistics were used to compare groups, with a p value < 0.05 as statistically significant. RESULTS: A total of 110 women were included in the study. Women that had undergone bariatric surgery were more likely to be white, Hispanic, and have higher pre-pregnancy and pregnancy BMIs. Vitamin D levels in breast milk decreases with increasing time from delivery regardless of surgical history (Table 2). Women in the bariatric surgery group had significantly higher 25(OH)D levels in transitional milk but similar levels in colostrum and mature milk when compared to CONCLUSION: Vitamin D levels in breast milk decreases with increasing interval from delivery. Interestingly enough, vitamin D levels were higher in transitional milk of women that had undergone bariatric surgery. Neonatal vitamin D supplementation should be considered when transitional and mature milk is utilized as the primary nutritional source regardless of maternal bariatric surgery history.